The Relationship Between Social Entrepreneurship, Corporate Social Responsibility and Organizational Performance in Social Economy Companies at Kurdistan Region of Iraq - Shirin Jamal Mohammad Rashid (QALAAI ZANIST JOURNAL, 2022)
This study is aimed at analyzing the relationship between social entrepreneurship, corporate social responsibility (CSR) and organizational performance in the context of economic and social economy companies in the Kurdistan Region of Iraq. Such incorporates investigating the mediating effects of CSR on the relationship between social entrepreneurship and organizational performance. Consequently, a structural equation modelling approach was applied in conjunction with Smart PLS to analyses questionnaire responses collected from 133 social companies in Erbil, Kurdistan. The study results show that social entrepreneurship is vital for enhancing the effectiveness of CSR activities and programs. Additionally, social entrepreneurship was noted as enhancing ways of improving an organization’s non-financial indicators leading to improved overall organizational performance. Similar suggestions were also provided regarding the positive interaction between CSR on the relationship between CSR and organizational performance. Lastly, the study findings implied that there is a need to supplement and reinforce social entrepreneurship with CSR programs and activities to enhance organizational performance. This includes engaging in corporate activities aimed at preserving the environment, protecting shareholders’ interests and meeting stakeholders’ expectations. Ideas provided in this study are originally derived from Erbil, Kurdistan and offered novel ideas about the structural connections linking social entrepreneurship, CSR and organizational performance. The study enhances understanding concerning the use and implications of social entrepreneurship in organizations.